Post-partum psychosis: a case report (UCC Student Medical Journal, 2024)
The patient (NS) is a 5 month post-partum 32 year old woman, G2P2, who presented to the Cork University Hospital (CUH) Emergency Department by ambulance. She presented to the ED distressed, anxious and confused. Her family history is significant for depression. Her personal history is significant for long periods of separation from her spouse and an increased workload and chores list at home, leading to high levels of stress and anxiety. Her past medical history includes two births, both caesarean and non-complicated. However, she contracted a SARS-CoV-2 infection prior to her most recent delivery.  Her eldest child is 6 years old and her most recent is 5 months. Prior to NS’s deterioration, she was described as level-headed, dependable, quiet, and overall an extremely competent mother. Her physical examination was non-contributory. Finally, on December 5th 2022, her condition improved. Her MSE showed a tidy appearance, non-paranoid body language, sequential speech, reactive mood, logical and non-paranoid thoughts, good insight about psychosis, excellent cognition, and low risk for harm to herself or others. In this case report, the biopsychosocial aspects of the patient’s recovery are discussed.
Keywords: psychiatric admission; Post-Partum; Case Report